Seasonality in Human Interest in Berry Plants Detection by Google Trends - Kotani, Ayumi; Shin, Nagai; Tei, Shunsuke; Makarov, Andrey; Gavrilyeva, Tuyara (Frontiers in Forests and Global Change, 2021)
The phenology of berry-producing plants, particularly their harvest season, is of human interest and also reflects the ecosystem’s response to the changing environment. We investigated the seasonal dynamics of human interest in berries growing in boreal, subarctic and Arctic ecosystems, mainly in Russia, based on internet search data via Google Trends. There is a typical and culture-specific pattern of seasonal variations in search volume concerning berries across Russia, Finland, and Canada. Generally, the seasonal peak of search corresponds to the common berry harvest season across these countries. We discussed the potential and limitation for detecting ecological factors from the internet search data, in which physical phenomena and socio-cultural aspects are fundamentally superimposed, and its applicability to phenological studies.